Assessment of Salivary Secretory Immunoglobulin A (sIg A) Level during Fixed Orthodontic Treatment - Shaymaa Sh. Taha (College of Dentistry/ University of Baghdad, 2016)
Background: The immune system of the oral cavity suffers alterations due to fixed orthodontic treatment which act as potent stimulus for oral secretory immunity. The aims of this study are to estimate the effect of fixed orthodontic appliance on the level of salivary sIgA at different time intervals, and to verify the gender difference. Materials and method: The patient's history, clinical examination, and fixed orthodontic appliances were placed for 30 Iraqi orthodontic adult patients had class II division 1 and/ or class I malocclusion (15 males and 15 females) aged 18-25 years old. The unstimulated whole saliva was collected from each sample immediately before wearing fixed appliance (control group T0 as base line), and after 2 weeks (T1),1 month (T2), and 1year (T3) of wearing fixed orthodontic appliance. The levels of salivary sIgA were measured by Enzyme Linked Immunosorbant Assay kit (ELISA). Results: The mean value of salivary sIgA was elevated at T1 and reached the peak at T2 followed by declined at T3 to reach near the normal value at T0 (base line). Repeated measure ANOVA test showed statistically highly significant difference among four time intervals. The Bonferroni test after repeated measure ANOVA test showed highly statistical significant difference between each two time intervals except between T0 and T3 show significant difference. In addition there were no significant gender differences. Conclusion: In this study one can conclude that fixed orthodontic appliance acts as an immunological stimulant in the oral cavity that changes the level of salivary sIgA which evaluate the immunity status in the oral cavity.